Asymmetries in leaf branch are associated with differential speeds along growth axes: A theoretical prediction. Issue 12 (13th October 2017) - Nakamasu, Akiko; Suematsu, Nobuhiko J.; Kimura, Seisuke
Abstract : Background: Morphogenesis, when accompanied by continuous growth, requires stable positional information to create a balanced shape in an organism. Evenly spaced branches are examples of such morphogenesis. Previously, we created a model that showed when a one‐dimensional (1D) ring (a boundary of a 2D field) was periodically deformed based on a stable, doubled iterative pattern during expansion; a nested, regularly spaced, symmetrically branched structure was generated. The characteristic divaricating pattern is common in the leaves of many plant species; however, the divarication symmetry was often broken. To evaluate this type of asymmetry, we investigated several species with dissected or compound leaves.Results: Sometimes these leaves showed asymmetries in the number of lobes or segments positioned on either side of the secondary axes. The direction of the asymmetry, i.e., which side of a secondary axis has more axes, appeared to be species‐specific.Conclusions: When different growth speeds along axes of a divaricating leaf were introduced into our previous model, robust and directed asymmetries were reproduced. The differences in growth speed could be predicted from the distributions of leaf segments in actual leaves. Developmental Dynamics 246:981–991, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Asymmetries of divaricate patterns in leaves of a wide range of plant species were analyzed. To explain the asymmetries of divarication, different speeds of growth axes were introduced into a previous mathematical model. The theoretically estimated degree of asymmetry was compared to that observed in actual leaves. The direction of asymmetry in a divaricate leaf and the predicted difference in growth speeds were compared.